Apparent exchange rate for breast cancer characterization. (29th February 2016) - Lasič, Samo; Oredsson, Stina; Partridge, Savannah C.; Saal, Lao H.; Topgaard, Daniel; Nilsson, Markus; Bryskhe, Karin
Abstract : Although diffusion MRI has shown promise for the characterization of breast cancer, it has low specificity to malignant subtypes. Higher specificity might be achieved if the effects of cell morphology and molecular exchange across cell membranes could be disentangled. The quantification of exchange might thus allow the differentiation of different types of breast cancer cells. Based on differences in diffusion rates between the intra‐ and extracellular compartments, filter exchange spectroscopy/imaging (FEXSY/FEXI) provides non‐invasive quantification of the apparent exchange rate (AXR) of water between the two compartments. To test the feasibility of FEXSY for the differentiation of different breast cancer cells, we performed experiments on several breast epithelial cell lines in vitro . Furthermore, we performed the first in vivo FEXI measurement of water exchange in human breast . In cell suspensions, pulsed gradient spin‐echo experiments with large b values and variable pulse duration allow the characterization of the intracellular compartment, whereas FEXSY provides a quantification of AXR. These experiments are very sensitive to the physiological state of cells and can be used to establish reliable protocols for the culture and harvesting of cells. Our results suggest that different breast cancer subtypes can be distinguished on the basis of their AXR values in cell suspensions. Time‐resolved measurements allow the monitoring of the physiological state of cells in suspensions over the time‐scale of hours, and reveal an abrupt disintegration of the intracellular compartment. In vivo, exchange can be detected in a tumor, whereas, in normal tissue, the exchange rate is outside the range experimentally accessible for FEXI. At present, low signal‐to‐noise ratio and limited scan time allows the quantification of AXR only in a region of interest of relatively large tumors. © 2016 The Authors. NMR in Biomedicine published by John Wiley & Sons Ltd. Abstract : Differences in diffusion rates between the intra‐ and extracellular compartments allow the non‐invasive quantification of the apparent exchange rate (AXR) between the two compartments. Experiments on several breast epithelial cell lines suggest that different breast cancer subtypes can be distinguished on the basis of their AXR values. In vivo, the AXR can be determined in a tumor, whereas, in normal tissue, AXR is outside the experimentally accessible range.